FACTORS ON THE FORMATION OF ORGANIZATIONAL MANAGEMENT STRUCTURES IN AGRICULTURAL ENTERPRISES - Ivanko , A.V.; Ksenofontov , M.M. (The actual problems of regional economy development, 2020)
The goal of the article is the research of the factors for formation of organizational management structures in agricultural enterprises. The subject of the article is separation the most significant for organizational management structures of agricultural enterprises factors and formation of the approach to the order of their consideration in management of any sectorial business entity. In the article the organizational management structure of business entities is understood as a holistic hierarchical system consisting of a set of organized units and levels of management. Within this set the organization of process of communication between them for the purpose of maintenance of effective process of functioning of the enterprise through interaction of components both with its internal, and with its external environment is carried out. The organizational management structure is formed with taking into account of certain factors. The generalization of the factors, that have influence to formation of the organizational management structures of agricultural enterprises, has been fulfilled. Wherein three key blocks has been separated: strategic or target, effectiveness and commodity assortment. Each of these blocks does not have an exclusive impact. The influence of the factors of each of these blocks should be considered in a balanced way when agreeing with each other. Emphasis is placed on the introduction of an integrated approach to the formation of organizational management structures. Management mechanisms are considered, that are more appropriate to apply to each of the selected blocks of factors.